An Evaluation of Eucalyptus Introduction Trials at New Forest, Dehra Dun - Gogate, M. G.; Dhaundiyal, U. C. (Indian Forester, 1988)
Eucalypts introduction trial at New Forest, which include 24 entries, is reviewed. The species are Eucalyptus astringens, bicostata, botryoides, camaldulensis, citriodora, dairympleana, diversicolor, ficifolia, grandis, 'hybrid', leucoxylon, longifolia, maculata, melanophloia, polybractea, populnea, robusta, rudis, sideroxylon, staigeriana,. tereticornis and 12 ABL. Based on their performance, species have been broadly categorised into three groups namely promising, average and failure, Varied performance of the species is attributed to comparability of locality factors of the donor and the recipient region i.e. Dehra Dun. Important factors contributing to success or failure are identified as comparability on the parameters of latitude, elevation, soil and climatic conditions particularly the temperature regime,frost and rainfall type. Among the species evaluated Eucalyptus tereticornis, melanophloia, saligna, longifolia, camaldulensis, dairyrmpleana, populifolia and robusta are indicated as promising species for the sub Himalayan zone.